Beyond Testis Size: Links between Spermatogenesis and Sperm Traits in a Seasonal Breeding Mammal - Pintus, Eliana; Ros-Santaella, José Luis; Garde, José Julián (PloS one, 2015)
Spermatogenesis is a costly process that is expected to be under selection to maximise sperm quantity and quality. Testis size is often regarded as a proxy measure of sperm investment, implicitly overlooking the quantitative assessment of spermatogenesis. An enhanced understanding of testicular function, beyond testis size, may reveal further sexual traits involved in sperm quantity and quality. Here, we first estimated the inter-male variation in testicular function and sperm traits in red deer across the breeding and non-breeding seasons. Then, we analysed the relationships between the testis mass, eight parameters of spermatogenic function, and seven parameters of sperm quality. Our findings revealed that the Sertoli cell number and function parameters vary greatly between red deer males, and that spermatogenic activity co-varies with testis mass and sperm quality across the breeding and non-breeding seasons. For the first time in a seasonal breeder, we found that not only is the Sertoli cell number important in determining testis mass (r = 0.619, p = 0.007 and r = 0.248, p = 0.047 for the Sertoli cell number assessed by histology and cytology, respectively), but also sperm function (r = 0.703, p = 0.002 and r = 0.328, p = 0.012 for the Sertoli cell number assessed by histology and cytology, respectively). Testicular histology also revealed that a high Sertoli cell number per tubular cross-section is associated with high sperm production (r = 0.600, p = 0.009). Sperm production and function were also positively correlated (r = 0.384, p = 0.004), suggesting that these traits co-vary to maximise sperm fertilisation ability in red deer. In conclusion, our findings contribute to the understanding of the dynamics of spermatogenesis, and reveal new insights into the role of testicular function and the Sertoli cell number on testis size and sperm quality in red deer.
Keywords: analýza hlavních komponent; velikost orgánu; Reproduction; roční období; Animals; Organ Size; rozmnožování; Spermatogenesis; mužské pohlaví; testis; Male; Principal Component Analysis; Seasons; zvířata; Testis; spermatogeneze